Parent SNAP‐IV rating of attention‐deficit/hyperactivity disorder: accuracy in a clinical sample of ADHD, validity, and reliability in a Brazilian sample - Danielle S. Costa; Jonas Jardim de Paula; Leandro F. Malloy‐Diniz; Marco A. Romano‐Silva; Débora M. Miranda (Brazilian Society of Pediatrics, 2019)
Objective: To investigate the psychometric properties of the short or multimodal treatment study version of the Swanson, Nolan, and Pelham, Version IV (SNAP‐IV) scale, which measures attention‐deficit/hyperactivity disorder and oppositional defiant disorder symptoms. Methods: Participants were 765 parents of children from 4 to 16 years old (641 non‐attention‐deficit/hyperactivity disorder and 124 attention‐deficit/hyperactivity disorder children) from Belo Horizonte, Brazil, who reported sociodemographic characteristics and answered the SNAP‐IV. Parents of the clinical sample also underwent the K‐SADS‐PL interview. Results: Age was significantly associated with SNAP‐IV hyperactivity‐impulsivity problems (r = −0.14), but not with inattention or oppositional defiant disorder. Sex was a significant influence on attention‐deficit/hyperactivity disorder and oppositional defiant disorder severity (all p < 0.001), with boys showing higher scores in the full sample, but not within the attention‐deficit/hyperactivity disorder group. Exploratory and confirmatory factor analysis supports a three‐factor structure of the SNAP‐IV scale. Moderate‐to‐strong correlations were found between SNAP‐IV and K‐SADS‐PL measures. All SNAP‐IV scales showed very high internal consistency coefficients (all above 0.91). SNAP‐IV inattention scores were the most predictive of attention‐deficit/hyperactivity disorder diagnosis (AUC: 0.877 for the averaging rating method and the raw sum method, and 0.874 for the symptom presence/absence method). Conclusion: The parent SNAP‐IV showed good psychometric properties in a Brazilian school and clinical sample. Resumo: Objetivo: Investigar as propriedades psicométricas da versão curta ou MTA da escala Swanson, Nolan e Pelham, versão IV (SNAP‐IV), que mede os sintomas do transtorno de déficit de atenção/hiperatividade e transtorno desafiador de oposição. Métodos: Os participantes incluíram 765 pais de crianças de 4 a 16 anos (641 crianças sem transtorno de déficit de atenção/hiperatividade e 124 com transtorno de déficit de atenção/hiperatividade) de Belo Horizonte, Brasil, que relataram características sociodemográficas e responderam o SNAP‐IV. Os pais da amostra clínica também foram submetidos à entrevista com K‐SADS‐PL. Resultados: A idade foi significativamente associada aos problemas de hiperatividade‐impulsividade no SNAP‐IV (r = −0,14), mas não à desatenção ou aos transtornos desafiadores de oposição. O sexo foi uma influência significativa na gravidade do transtorno de déficit de atenção/hiperatividade e transtorno desafiador de oposição (todos os p < 0,001), os meninos apresentaram escores mais altos na amostra completa, mas não no grupo de transtorno de déficit de atenção/hiperatividade. A análise fatorial exploratória e confirmatória apoia uma estrutura de três fatores da escala SNAP‐IV. Foram encontradas correlações moderadas a fortes entre as medidas dos instrumentos SNAP‐IV e K‐SADS‐PL. Todas as escalas do SNAP‐IV mostraram coeficientes de consistência interna muito altos (todos acima de 0,91). Os escores de desatenção do SNAP‐IV foram os mais preditivos do diagnóstico de transtorno de déficit de atenção/hiperatividade (AUC - área sob a curva ROC: 0,877 para o método de classificação da média e o método da soma bruta e 0,874 para o método de presença ou ausência de sintomas). Conclusão: A avaliação do SNAP‐IV pelos pais apresentou boas propriedades psicométricas em uma escola brasileira e amostra clínica. Keywords: Attention‐deficit/hyperactivity disorder, Oppositional defiant disorder, Psychological assessment, Clinical psychiatry, Psychometrics, Palavras‐chave: Transtorno de déficit de atenção/hiperatividade, Transtorno desafiador de oposição, Avaliação psicológica, Psiquiatria clínica, Psicometria